2009
DOI: 10.1111/j.1468-0297.2008.02241.x
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Air Quality Using the Life Satisfaction Approach

Abstract: I use the life satisfaction approach to value air quality, combining individual-level panel and high-resolution SO 2 data. To avoid simultaneity problems, I construct a novel instrument exploiting the natural experiment created by the mandated scrubber installation at power plants, with wind directions dividing counties into treatment and control groups. I find a negative effect of pollution on well-being that is larger for instrumental variable than conventional estimates, robust to controls for local unemplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
375
3
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(395 citation statements)
references
References 61 publications
12
375
3
5
Order By: Relevance
“…Apart from looking at the usual happiness determinants we will look at some additional factors, viz., religiosity, immigration, ethnicity, and the effects of war. In the literature there are many studies on the impact of religiosity on happiness, but most of those studies are found in the psychological and sociological journals (see Cohen (2002), Clark and Lelkes, (2005), (2009( ), Helliwell, (2003, Dehejia, DeLeire, and Luttmer, (2007), Heady et al (2010), Snoep (2008)). The main result of these studies is that religiously more active persons (mostly defined in terms of church attendance) tend to be happier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from looking at the usual happiness determinants we will look at some additional factors, viz., religiosity, immigration, ethnicity, and the effects of war. In the literature there are many studies on the impact of religiosity on happiness, but most of those studies are found in the psychological and sociological journals (see Cohen (2002), Clark and Lelkes, (2005), (2009( ), Helliwell, (2003, Dehejia, DeLeire, and Luttmer, (2007), Heady et al (2010), Snoep (2008)). The main result of these studies is that religiously more active persons (mostly defined in terms of church attendance) tend to be happier.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we use the so-called POLSoperationalization (Van Praag andFerrer-i-Carbonell (2004, 2008) and Luechinger (2009)). This method is inspired by the observation that if we use the responses 1,2,3,4 in (2.1) as the variable to be explained, the left-hand term is bounded, while the right-hand side may attain any value on the real axis.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate the economic importance, studies in this field often provide a transformation of non-monetary effects into equivalent monetary figures (e.g., Carroll et al 2009;Luechinger 2009;Luechinger and Raschky 2009;Kountouris and Remoundou 2011). 4 While the study here is also motivated by the idea that subjective well-being is generally translatable and measurable in economic terms, the prime motivation comes from a different and more political viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…El uso de datos de bienestar subjetivo para la valoración económica ambiental ha ganado popularidad (Van Praag & Baarsma, 2005;Luechinger, 2009;Tsurumi & Managi, 2015). A diferencia de los enfoques de preferencias declaradas, en los que los individuos expresan su disposición a pagar (DAP) por una mejora ambiental hipotética, el enfoque de satisfacción con la vida se basa en la asociación estadística entre el bienestar subjetivo expresado por el individuo e indicadores de calidad ambiental, al tiempo que se controla por otros factores como el ingreso y las características socio-demográficas del encuestado.…”
Section: Valoración Económicaunclassified